Transcranial optical vascular imaging (TOVI) of cortical hemodynamics in mouse brain - Kalchenko, Vyacheslav (Sci Rep, 2014)
In vivo imaging of cerebral vasculature and blood flow provides highly valuable information for clinicians as well as researchers. Nevertheless, currently available methods are complex, time-consuming and expensive. Here, we present a novel, minimally invasive method for vascular imaging through the sufficiently transparent intact skull of young mice. Our method combines laser speckle and fluorescent imaging with dynamic color mapping and image fusion. Quickly generated wide-field images present clear visual information on blood flow and perfusion in the cerebral cortex and meninges. The ability of the method to visualize hemodynamic changes is demonstrated by induced occlusion of the middle cerebral artery. The compact and easily operated system comprises of several pieces of standard and affordable laboratory equipment. This simple, robust and inexpensive method may become an important tool for assessment of brain hemodynamics in preclinical studies.